Mortality related to COVID-19 in kidney transplant recipients, dialysis patients and patients with chronic kidney disease: a cohort study - Sara El Maakoul; Yassir Tahri; Ouzeddoun Naima; Benamar Loubna (The Egyptian Journal of Internal Medicine)
Abstract Background Coronavirus disease, emerging in December 2019, is a viral infection with varied clinical presentations, often severe in those with co-morbidities like chronic kidney disease. Despite the WHO declaring the end of the public health emergency, the risk of new, more serious variants is also very real. Hence the interest in taking advantage of the momentum created since the emergence of COVID-19. Aim Determine the prognostics and mortality in patients with chronic kidney disease and SARS-CoV-2 infection. Methods This is a retrospective cohort study that was conducted during the COVID-19 pandemic period, between March 2020 and November 2021. We included patients with chronic kidney disease and confirmed SARS-COV-2 infection, managed by a nephrologist requiring or not hospitalization. Results We identified 250 patients with confirmed COVID-19 disease, 44% with chronic kidney failure. The mean age of our patients was 60 ± 16.2 years, with a sex ratio of 1.4. Functional signs suggestive of COVID-19 reported by our patients were variable and dominated by fever and dyspnea. Death was observed in 40% of cases. In multivariable analysis, the variables statistically associated with death (p < 0.05) were dyspnea, temperatura ≥ 39, use of methylprednisolone, and percentage of lung involvement on chest CT. However, the use of azithromycin and vitamin C is significantly associated with a better outcome. Conclusion Patients with chronic kidney disease are immunocompromised and therefore predisposed to infection with SARS-CoV-2 and the development of severe forms. Hence the need for early diagnosis and appropriate management.